Gathering “Mouse Roots,” Among the Naukan and Chukchi of the Russian Far East - Jernigan, Kevin; Belichenko, Olga; Kolosova, Valeria; Orr, Darlene; Pupynina, Maria (Ethnobiology Letters, 2019)
The authors worked from 2014–2016, with 67 Naukan and Chukchi participants in six villages on the subject of “mouse roots,” a category of edible plants, including tubers of five species, taken from caches of Microtus voles. Only eight out of 44 Chukchi and none of the Naukan respondents said that they still actively gather these foods. However, 43 out of 44 Chukchi and 21 out of 23 Naukan participants still possess specific knowledge of the process, for example: how to find nests, proper techniques and etiquette for gathering, storage, preparation, or botanical identity of species found. This reflects the rapid cultural changes that occurred during the Soviet period, including collectivization and consolidation of the population into larger villages. The maintenance of knowledge about resources that no longer play a large role in subsistence never-the-less aids in the resilience of local people to potential economic hardship and food insecurity. This particular relationship between humans, rodents, and plants provides an opportunity to examine the strengths and limitations for applying the concept of perspectivism in this cultural setting. These Chukotkan “mouse root” traditions show commonalities with similar practices among the neighboring Iñupiaq and Central Alaskan Yup’ik communities. Most notably, species gathered from rodent nests are similar on both sides of the Bering Strait as are rules for how to show proper respect to the animals when gathering. However, methods of preparation differ significantly between Chukotkan and Alaskan cultures.